La France inchangée -Soumission de Houellebecq : roman de continuité - Courteau, Clément (2018)
Michel Houellebecq’s latest novel, Soumission, tells the story of a muslim’s party’s victory at the presidential elections in France. In the midst of the fear-laden solidarity that followed the events at Charlie Hebdo, the novel could be read as a confirmation of the danger Islam represents for the French republic. But in the story narrated by its hero François, the state’s, and later his, conversion to Islam are seen as positive events, that set up a social structure where their repressed desires can be openly pursued. By showing that the imagined, reified Islam which France fears, turns out to be a way of affirming and legitimizing its deepest desires, Houellebecq shows that far from being the radical alterity it is often depicted to be when seen through the lens of terrorism, Islam, as caricatured by islamophobia, is the next step in France’s civilisational development.